2008
DOI: 10.1196/annals.1429.020
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Issues in Adolescents with Physical and Developmental Disabilities

Abstract: Puberty and menstruation are difficult issues for teens with disabilities and for their families as well. Irregular bleeding, mood swings, and problems with hygiene often complicate the delicate balance in the lives of these adolescents. The care provider is asked to help with the pubertal transition and the issues surrounding menstruation and reproductive health. This review will concentrate on the issues concerning menstruation that need special focus in teens with developmental disability (DD). The impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…5 Developmental disability often makes menstrual hygiene challenging and may lead families to seek menstrual suppression from health care providers. 6 One single center retrospective chart review of 72 of adolescent girls (age range 8e17 years) with developmental disability presenting to a gynecological clinic found that 67% were seeking menstrual suppression, most commonly because of hygiene and coping concerns. 7 Menstrual hygiene issues could potentially cause school absenteeism, negatively impacting the girl's ability to learn and creating additional pressures on her caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…5 Developmental disability often makes menstrual hygiene challenging and may lead families to seek menstrual suppression from health care providers. 6 One single center retrospective chart review of 72 of adolescent girls (age range 8e17 years) with developmental disability presenting to a gynecological clinic found that 67% were seeking menstrual suppression, most commonly because of hygiene and coping concerns. 7 Menstrual hygiene issues could potentially cause school absenteeism, negatively impacting the girl's ability to learn and creating additional pressures on her caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…230 Menstrual control and suppression is commonly achieved with COCs, transdermal patches, DMPA, and levonorgestrel IUDs. 77,231,232 Continuous or extended cycles of COCs is a common approach, 231,232 and there are reports of successful use of 52-mg levonorgestrel IUDs in adolescent patients. 76,77,80 Surgical approaches (tubal ligation, endometrial ablation, or hysterectomy) are rarely necessary and present special ethical and legal issues.…”
Section: Adolescents With Disabilitiesmentioning
confidence: 99%
“…A detailed discussion of menstrual management for adolescents with disabilities can be found in recent review articles as well as professional consensus statements. [231][232][233] Adolescents With Obesity…”
Section: Adolescents With Disabilitiesmentioning
confidence: 99%
“…The major concerns of a family with a girl undergoing puberty in the context of disability [33] are the three questions: can we stop periods, will there be side effects, and how will we address contraception? Options for management include the oral contraceptive pill, use of transdermal oestrogen, implantable progestogen or a progestogen-bearing intrauterine device [34,35].…”
Section: Pubertal Problemsmentioning
confidence: 99%